(untitled) (SCIENCE TIME JOURNAL, 2023)
The era of the Somanites, which is recognized as an integral page in the history of our country, is distinguished by the fact that during this period, peace policy prevailed in the country, and science and culture flourished. During this period, dozens of scholars lived and worked in our country, such as Ibn Sina, a famous thinker, and theologian Abu Mansur Moturidi, who gained great fame in Islamic sciences. Also, during this period, Islamic sciences developed in our country and many centers of knowledge, including schools such as "Dor alJuzhoniya", "Dor al-Iyodiya", and "Bukhara Fiqh School" were operating. This period is also distinguished by the fact that inter-ethnic harmony, religious tolerance and religious tolerance were stable in the country during this period. In this article, we aim to provide information about the history of this stability during the Samanid era, which ruled Movarounnahr as a strong empire for about a century and a half.